Crystallization technology: selective polymorphism of L-glutamic acid in anti-solvent crystallization - Ngoc Phuong, Nguyen Thi; Quang, Khuu Chau; Tuyet, Nguyen Dinh; Dieu Thuy, Tran Thi; Thanh Huyen, Trinh Thi; Hong Nhan, Le Thi; Thao, Phan Thanh; Tuan, Nguyen Anh (Vietnam Journal of Chemistry, 2015)
The selective polymorphism of L-glutamic acid was firstly investigated in anti-solvent crystallization with a high productivity. When the ratio of feed solution and anti-solvent was varied from 90:10 to 80:20, the pure metastable α-form crystal was crystallized at 300C, 18.5g/l feed concentration and 360rpm of agitation speed. However, when the ratio of feed solution and anti-solvent was varied from 70:30 to 40:60, the mixture of α-form and b-form crystal product was precipitated. Further decreasing the ratio of feed solution and anti-solvent from 30:70 to 10:90, the only pure stable b-form crystal was crystallized. The results indicated that the supersaturation determined by the ratio of feed solution and anti-solvent was a key factor to impact on the nucleation process, in which the nucleation of α-form and b-form was favorably crystallized at a low and high supersaturation, respectively, which resulted in the selective polymorphism of L-glutamic acid in the anti-solvent crystallization. Keywords. Crystallization, polymorphism, phase transformation, anti-solvent crystallization